The Application of Educational Administration Functions in Improving the Quality of Elementary Schools - Ita Rusiana; Imam Muhayat (Tahta Media Group, 2026)
This study aims to analyze and describe the implementation of educational administrative functions based on the POAC framework (Planning, Organizing, Actuating, and Controlling) and its contribution to improving school quality at SDIU Sahabat Madiun, East Java. School quality is measured through improvements in teacher competence and student academic achievement in accordance with the National Education Standards (SNP). This study employs a qualitative descriptive method. Data collection techniques included participatory observation over a one-month period, semi-structured interviews with the principal and teachers, and a documentary review of the School Work Plan (RKS) and school program documents. Data analysis utilized the Miles and Huberman model, which encompasses data reduction, data presentation, and drawing conclusions. The results of the study indicate that the four POAC functions have been implemented systematically and in an integrated manner. The Planning function is realized through the establishment of measurable quality targets via the RKS and RKAS. The Organizing function is reflected in the formation of an accountable internal quality assurance team (SPMI). The Execution function is carried out through the principal’s transformational leadership, accompanied by in-house training programs for teachers. The Monitoring function is carried out through continuous academic supervision, in which evaluation results are used as feedback for the next planning cycle. It is concluded that the application of POAC-based educational administration functions contributes significantly to the continuous improvement of quality at SDIU Sahabat.